Mechanobiology of cancerogenesis - Raudenská, Martina; Navrátil, Jiří; Gumulec, Jaromír; Masařík, Michal (Klinicka onkologie, 2021)
BACKGROUND: Within the tumour microenvironment, tumour cells are exposed to different mechanical stimuli such as compression stress, cell-cell and cell-extracellular matrix traction forces, interstitial fluid pressure, and shear stress. Cells actively sense and process this information by the mechanism of mechanotransduction to make decisions about their growth, motility, and differentiation. Indeed, the mechanical properties of the tumour microenvironment can deeply influence the behaviour of cancer cells and promote cancerogenesis. During tumour progression, desmoplasia arises and a positive feedback loop between the stiffening extracellular matrix and the properties enabling tumour expansion is established. Tumour cells can use mechanic stimuli to promote proliferation, increase their migratory and invasive potential, and induce therapeutic resistance. Mechanobio-logy is a progressive multidisciplinary field which studies how mechanical forces influence the behaviour of cells or tissues and may provide some interesting targets for cancer therapy. PURPOSE: In this review, we discuss the mechanical properties of cancer cells and describe the tumour promoting effect of the transformed extracellular matrix. We propose that the differences in the mechanobio-logy of cells and extracellular matrix are significant enough to facilitate tumorigenesis and may provide interesting targets for cancer therapy.
Keywords: therapy resistence; nádorová transformace buněk; nádorové mikroprostředí; buněčný převod mechanických signálů; Neoplasms; shear stress; cancer; biofyzika; Cell Transformation, Neoplastic; mechanobiology; malignancy; extracelulární matrix; Animals; lidé; Biophysics; Humans; zvířata; Mechanotransduction, Cellular; Extracellular Matrix; nádory; mechanotransduction; Tumor Microenvironment; extracellular matrix